Comparison of chemical contents of sheabutter extracted from locally designed machine - Inegbenebor, A. I.; Inegbenebor, A.O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2004)
As elemental contents of sheabutter play a vital role in various physiological and metabolical activities in the human body, it is necessary to compare the chemical contents of sheabutter extract from different procedures in order to identify the most important extraction procedure. Sheabutter extracted using a locally developed machine was compared with the composition of extract from two other techniques using a soxhlet extractor and the traditional procedure. The result shows increasing recoveries of most of the elements on progressing to the design machine and soxhlet apparatus from traditional procedure. The chemical analysis results showed the amount of lead, mercury, manganese, iron, copper, calcium, iodine, magnesium and phosphorus present in the sheabutter. The amounts of Ca, Fe and Pb are as high as 22.8 µgl-1. This work also found that the levels of elemental composition in the extracts of 22.8 µgl-1 sheabutter from modern machine are more than those from the traditional extracting method of 16.2 µgl-1. Possible reasons and implication of those findings are discussed.